Performances evaluation of inverse kinematic models of a compact bionic handling assistant - Singh, Inderjeet; Lakhal, Othman; Amara, Yacine; Coelen, Vincent; Pathak, Pushparaj Mani; Merzouki, Rochdi (2017 IEEE International Conference on Robotics and Biomimetics (ROBIO), 2017)
Inverse Kinematic Model (IKM) is very crucial for real-time control of a robot for any application. Computing the IKM of continuum manipulators is a challenging task. Two types of methods exists; quantitative methods describing a model-based approach; and qualitative methods, based on learning approach. As quantitative methods are based on mathematical expression, they are more flexible for extension (increase in number of sections or collaboration between more than one manipulator). In this paper, two quantitative approaches based on Newton Raphson iterative method and Damped Least Square method, are proposed for Compact Bionic Handling Assistant (CBHA) manipulator to solve inverse kinematics directly using Forward Kinematic Model (FKM). Experimental validation is done for these methods as well as they are compared with the existing approaches named Hybrid approach and Neural Network based learning approach.